Aux commencements - Création et temporalité dans la Bible et dans son contexte culturel : Collected Essays on Creation and Temporality in Ancient Near Eastern and Biblical Texts.. - Achenbach, Reinhard (Harrassowitz Verlag, 2019)
In February 2017 an international colloquium was held in Paris on the issue of this volume, entitled In the Beginning. Creation and Temporality in the Bible and in its Cultural Context. The papers from this colloquium together with some essays from the last period of research are now presented in this volume. The collection contains different approaches and perspectives with respect to the issue, philological investigations on forms to describe initiative actions or events, essays on the concept of creation that intends to describe beginnings in the classical meaning, on myths on decline and recreation and on their historical and sociological function, and studies about the liturgical and cosmological meaning of calendars. With contributions by I. Klock-Fontanille (Hethitology), N. Ziegler and L. Mari (Assyriology), R. Hawley (Ugaritic Studies) and J. Kellens (Iranian Studies) as well as on the texts of the Old Testament (O. Artus, R. Achenbach, R. Müller, J.M. Robker, S. Ramond, J.-S. Rey) and the New Testament (C. Raimbault, H. Löhr).
Keywords: Bible. -- Genesis -- Criticism, interpretation, etc.; Bible. -- Genesis; Creation -- Mythology.; Mythology, Assyro-Babylonian.; Assyro-Babylonian literature.; Zoroastrianism.; Mythologie assyro-babylonienne.; Littérature assyro-babylonienne.; Zoroastrisme.; Assyro-Babylonian literature; Creation -- Mythology; Mythology, Assyro-Babylonian; Zoroastrianism; Criticism, interpretation, etc.